PENGARUH FUNGSI PENGAWASAN DAN PEMBERIAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN PENYADAP KARET DI KEBUN BALAI PENELITIAN SEMBAWA - Astri Novalia; Zunaidah .; Yuliansyah M. Diah (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
This study is the research about the function of monitoring, incentives and work productivity of rubber tappers employee at the farm of Research Center Estate Sembawa. The purpose of this study is to determine whether the monitoring function and incentives that effect to work productivity. The study was using qualitative methods associated with the quantitative analysis of multiple regression analysis to the relationship between the variables being tested look. The result from this study has the relationship between monitoring function with work productivity as 0.328 or 33%. Then incentives also have a relationship with work productivity as 0.599 or 60%. This means that there have other factors which can influence work productivity at 7%.